Photovoltaic array design for laser power transmission in space applications - Giovanni Cichelli; Pierluigi Morsaniga; Giuseppe Gervasio; Paolo Laporta; Nicola Coluccelli (JPhys Energy)
Wireless power transmission through lasers can revolutionize energy delivery methods, providing continuous power supply to satellites, unmanned aerial vehicles, and space stations, where traditional power sources are impractical. The receiver uses photovoltaic (PV) cell technology. However, while modern PV panel designs perform well under uniform white-light illumination, such as sunlight, they face limitations when exposed to the non-uniform, typically Gaussian, and highly-monochromatic radiation produced by a laser source. The article focuses on the design of PV panels specifically engineered for power transmission via laser, by taking into account the Gaussian intensity distribution across the panel along with the variations of the electrical parameters due to thermal effects. Two designs are proposed, based on PV cells arrangements in a Ring- or Tree-Shaped geometry, aimed at optimizing energy conversion efficiency, while complying with the mechanical and electrical constraints required by space applications. Numerical simulations predict a maximum conversion efficiency of 37% at an incident laser power of 5 kW and a peak laser intensity of 500 W m ^−2 , approaching the theoretical limit of 42.3% for a single PV cell operated at 1 W cm ^−2 .